Brief segments of neurophysiological activity enable individual differentiation - Jason da Silva Castanheira (Nature Portfolio, 2021)
We all have the intuition that our brain makes us unique. Here, the authors show that seconds of brain activity are sufficient to differentiate an individual, even when recorded weeks or months apart.